2019
DOI: 10.14744/anatoljcardiol.2019.90349
|View full text |Cite
|
Sign up to set email alerts
|

Association with serum adropin levels and isolated coronary artery ectasia in patients with stable angina pectoris

Abstract: Association between serum adropin levels and isolated coronary artery ectasia in patients with stable angina pectoris Objective: Dilation of one or more coronary artery segments to a diameter at least 1.5 times that of a normal adjacent segment is referred to as coronary artery ectasia (CAE). Adropin is a protein involved in endothelial function and is shown to have a protective effect on the regulation of cardiac functions. Atherosclerosis and endothelial dysfunction play an important role in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
(37 reference statements)
1
6
0
1
Order By: Relevance
“…As the detailed pathogenesis of CAE and CSF are still uncertain, hypothesis including chronic in ammation, atherosclerosis, endothelial dysfunction and oxidative stress may have participated in the pathological processes of the two diseases [1][2][3][4][5][6][7][8][9][10][11][12]14] . Many studies focused on in ammation; however, other aspects of research were relatively few.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the detailed pathogenesis of CAE and CSF are still uncertain, hypothesis including chronic in ammation, atherosclerosis, endothelial dysfunction and oxidative stress may have participated in the pathological processes of the two diseases [1][2][3][4][5][6][7][8][9][10][11][12]14] . Many studies focused on in ammation; however, other aspects of research were relatively few.…”
Section: Discussionmentioning
confidence: 99%
“…The rst limitation relates to its retrospective design. Some risk factors, such as the matrix metalloproteinase family, tissue inhibitors of metalloproteinases [29,30] and adropin [3] , which have a signi cant role in CAE development, couldn't be collected. Second, multivariable logistic regression analyses were performed to identify independent predictors of CSF in CAE; however, it was impossible to control for unknown confounders.…”
Section: Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first limitation relates to its retrospective design. Some risk factors, such as the matrix metalloproteinase family, tissue inhibitors of metalloproteinases [ 34 , 35 ] and adropin [ 2 ], which play a significant role in CAE development, could not be examined. Second, multivariable logistic regression analyses were performed to identify independent predictors of CSF in CAE; however, it was impossible to control for unknown confounders.…”
Section: Limitationsmentioning
confidence: 99%
“…Adropin has an important role in maintaining energy homeostasis and insulin sensitivity, which has been proved to attenuated the development of atherogenesis in animal experiment [6][7][8]. Low serum adropin level was also associated with stable angina pectoris, acute myocardial infarction and the severity of coronary atherosclerosis [9][10][11][12][13][14]. Fujie S et al also found a negative correlation between serum adropin level and carotid arterial stiffness [15].…”
Section: Introductionmentioning
confidence: 99%